Clinical features and comorbidities of Epstein–Barr virus infection in childhood-onset systemic lupus erythematosus with a focus on macrophage activation syndrome: a cross-sectional study of 200 patients - Wang, Hongye; Zhouyang, Mengqian; Yang, Xiran; Zhang, Jia; Yan, Helin; Zhang, Yingyi; Li, Li; Zhao, Bo (Frontiers in Immunology, 2026)
ObjectiveThis study aimed to investigate the prevalence of Epstein–Barr virus (EBV) infection in patients with childhood-onset systemic lupus erythematosus (cSLE) in Southwest China and to explore its associations with clinical manifestations, laboratory parameters, disease activity, and complications, particularly macrophage activation syndrome (MAS).MethodsA single-center, retrospective, cross-sectional study was conducted, enrolling 200 cSLE patients newly diagnosed at the Yunnan Provincial Children’s Medical Center between January 2022 and June 2024. Based on EBV DNA levels tested at baseline (disease diagnosis) using real-time quantitative PCR (viral load ≥ 500 copies/mL defined as positive), patients were categorized into an EBV-positive group (n = 65) and an EBV-negative group (n = 135). Demographic data, clinical manifestations, laboratory findings, disease activity (SLEDAI-2K score), and complications [MAS, lupus nephritis (LN), neuropsychiatric SLE (NPSLE), lupus pneumonitis] were compared between the two groups. Binary logistic regression analysis was used to identify independent risk factors for MAS.ResultsThe prevalence of EBV infection was 32.5% (65/200). Compared to the EBV-negative group, the EBV-positive group had significantly higher frequencies of neurological symptoms (66.2% vs. 45.2%, P = 0.007) and serous cavity effusion (60.0% vs. 43.7%, P = 0.035). Laboratory analysis revealed significantly lower levels of complement C3 (P = 0.032) and C4 (P = 0.009), lower serum albumin (P = 0.025), and higher blood urea nitrogen (BUN) (P = 0.014) in the EBV-positive group. Most critically, the incidence of MAS was significantly higher in the EBV-positive group (15.4% vs. 6.7%, P = 0.049). Multivariate analysis confirmed that EBV infection was an independent risk factor for MAS (OR = 2.90, 95% CI: 1.01–8.69, P = 0.0497), while a higher platelet count was a protective factor (OR = 0.25, 95% CI: 0.07–0.75, P = 0.0218). No significant differences were found between the groups regarding the prevalence of LN, NPSLE, lupus pneumonitis, or the overall SLEDAI-2K score.ConclusionEBV infection is independently associated with an increased risk of MAS in cSLE patients and is linked to more pronounced complement consumption and specific clinical manifestations such as neurological symptoms and serositis. This study underscores the importance of EBV screening in cSLE patients for the early vigilance and management of MAS.